Temporal Trends in the Rate of Revision Total Knee Arthroplasty for Prosthetic Joint Infection - Anne R. Bass, MD; Bella Mehta, MBBS; Peter K. Sculco, MD; Yi Zhang, MS; Huong T. Do, MA; Katharine Kayla J. Glaser, BA; Carlos Aude, BA; Alberto V. Carli, MD; Mark P. Figgie, MD; Susan M. Goodman, MD (Arthroplasty Today, 2024)
Background: Perioperative practices have been introduced over the last decade to decrease the risk of periprosthetic joint infection (PJI). We sought to determine whether rates of revision total knee arthroplasty (TKA) for PJI decreased during the period 2006-2016. Methods: This observational cohort study used data from the New York Statewide Planning and Research Cooperative System to identify patients undergoing TKA in 2006-2016. Data through 2017 were used to determine if patients underwent revision TKA for PJI (including debridement, antibiotics and implant retention) within 1 year of the primary surgery. A generalized estimating equation model, clustered by hospital, was used to examine the impact of time on likelihood of revision TKA for PJI. Results: In 2006-2016, 233,165 primary TKAs performed were included. Mean age was 66.1 (standard deviation 10.3) years, and 65% were women. Overall, 0.5% of the patients underwent revision TKA for PJI within 1 year of surgery. The generalized estimating equation model showed that for primary TKA performed in 2006-2013, year of surgery did not impact the likelihood of revision TKA for PJI (odds ratio 1.00, 95% confidence interval 0.97-1.03, P = .9221), but that for primary TKA performed in 2014-2016, the likelihood decreased by year (odds ratio 0.76, 95% confidence interval 0.66-0.88, P = .0002). Conclusions: The likelihood of revision TKA for PJI was stable from 2006 to 2013 but declined during the period 2014-2016 across patient and hospital categories. This decline could be due to infection mitigation strategies or other unmeasured factors.